2023
DOI: 10.1108/bfj-12-2022-1070
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumers' attitude and intent to purchase organic food in an emerging market context: a pre-/post COVID-19 pandemic analysis

Youssef Chetioui,
Irfan Butt,
Hind Lebdaoui
et al.

Abstract: PurposeFollowing the COVID-19 pandemic, the upward trend of organic food (OF) consumption is no longer restrained to western markets but has also extended to emerging markets in different parts of the world. Still, extent post-pandemic literature has devoted little attention to the factors shaping consumers' intent to purchase organic food in developing markets. The current research empirically investigates the antecedents of consumers' attitude and intent to purchase organic food in an emerging market context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Previous research supported the idea that perceived complexity has a detrimental impact on customers' decisions to use Islamic banking services (Jamshidi and Hussin, 2013;Thambiah et al, 2012). On the other hand, Chetioui et al (2023b) found that simplicity is positively influencing the choice of Islamic Products adoption. Building on the findings of earlier studies, we put forth the following hypo paper: H2 -Perceived complexity has a negative impact on the attitude toward Islamic Takaful.…”
Section: Hypotheses Developmentmentioning
confidence: 70%
“…Previous research supported the idea that perceived complexity has a detrimental impact on customers' decisions to use Islamic banking services (Jamshidi and Hussin, 2013;Thambiah et al, 2012). On the other hand, Chetioui et al (2023b) found that simplicity is positively influencing the choice of Islamic Products adoption. Building on the findings of earlier studies, we put forth the following hypo paper: H2 -Perceived complexity has a negative impact on the attitude toward Islamic Takaful.…”
Section: Hypotheses Developmentmentioning
confidence: 70%